Comparison of Non-alcoholic Fatty Liver Disease Indexes and Hepatic Ultrasonography as Predictors of Hepatosteatosis in Patients with Obesity - Feray Akbaş; Işıl İşel; Hanife Usta Atmaca; Mehmet Emin Pişkinpaşa (Bagcilar Medical Bulletin, 2024)

(untitled)
Objective: Obesity affects 60% of adults in Europe. Non-alcoholic fatty liver disease (NAFLD) is one of the most prevalent obesity consequences that increase cardiovascular and hepatic morbidity and mortality. Here; it was aimed to compare NAFLD indexes with hepatic ultrasonography (USG) and determine whether these indexes could be used as predictors of hepatosteatosis in patients with obesity. Method: Eighty randomly chosen patients from our obesity center were included in the study. Patients ≥18 years-old, having files with all research parameters were included and having acute/chronic hepatic disease/malignancy, getting any kind of treatment for hepatosteatosis, having alcohol consumption above recommended amounts were excluded. All patients’ age, gender, weight, height, body mass index (BMI), waist circumference, gasting blood glucose, high-density lipoprotein, triglyceride, low-density lipoprotein, insulin, alanine transaminase (ALT), aspartate aminotransferase, gamma-glutamyl transferase, hepatic USG results, accompanying diseases and medicines were recorded. Nonalcoholic fatty liver disease indexes: Hepatosteatosis index (HSI), visceral adiposity index (VAI), fatty liver index (FLI) and lipid accumulation product index (LAP) were calculated. Results were evaluated using SPSS program. Results: Sixty-five female and 15 male, totally 80 people with obesity were included in the study. Mean age was 44.29±12.82 years in women and 38.27±12.88 years in men. In general population HS rates were: No hepatosteatosis 10%, first degree 17.05%, second degree: 58.75% and third degree: 13.75%. Weight, WC, ALT, diabetes mellitus, hypertension, being on medication for accompanying diseases and alcohol consumption within recommended rates were higher in HS(+) group when compared to HS(-) group. When HS levels were compared with mean NAFLD index values, there was statistically significant difference for HSI mean group values. There was no statistically significant difference for other NAFLD indexes. There was a positive correlation between BMI and LAP, FLI and HSI. There was no significant correlation between BMI and VAI. Conclusion: As NAFLD is a strong predictor of cardiometabolic morbidity and mortality, it is important to make a diagnosis before progression in people living with obesity and simple non-invasive screening/diagnostic tools are needed for this purpose. VAI, LAP, FLI, HSI are easily calculated scientific models that are found to be predicting NAFLD. Although we could only partially found this prediction, they could be used sufficiently after national validation studies that determine the cut-off values and help to achieve prevention of NAFLD-related complications with early diagnosis.